Implementation of WEGOS with TikTok in Problem-Based Differentiated Learning to Enhance Self-Efficacy - Gugun Manosor Simatupang; Mujahidawati Nur Mujahidawati; Febbry Romundza; Novferma Novferma (Universitas Lambung Mangkurat, 2026)
This study investigated the effectiveness of implementing WEGOS (Web Google Sites) integrated with TikTok within a Differentiated Learning framework to improve students' academic self-efficacy. A quasi-experimental pretest-posttest control group design was conducted involving 84 second-year students of the Mathematics Education Study Program at the University of Jambi. The experimental group received instruction via WEGOS (Web Google Sites) supported by TikTok-based learning videos in differentiated problem-solving activities, while the control group received conventional instruction. Data were collected using an adapted Academic Self-Efficacy Scale consisting of 20 Likert-type items. The results showed that the experimental group achieved a higher mean posttest score (84.21) compared to the control group (74.35), with a statistically significant difference (p < 0.05). The calculated effect size (Cohen's d = 0.95) indicated a substantial practical impact. These findings suggest that integrating a structured web-based learning environment and short-form social media content in differentiated problem-based learning significantly strengthens students' self-confidence in managing academic tasks. This study contributes to the development of technology-supported differentiated pedagogy in higher education and highlights the importance of aligning digital tools with intentional instructional design to support affective learning outcomes.